Enhancing Anthocyanin Butterfly Pea Stability using Encapsulation: A Scoping Review of Coating Materials and Techniques - Firdaus, Jihan; Indarto, Dono; Listyawati, Shanti (Media Publikasi Cendekia Indonesia, 2025)
Butterfly pea flowers are rich in anthocyanin and have therapeutic benefits, particularly due to their antioxidant properties. However, their use in the food and pharmaceutical industries is still limited due to their low stability in environmental conditions, which causes degradation, decreased stability and bioavailability. Nanoencapsulation is a potential method for improving the stability and effectiveness of anthocyanin. This review aims to identify various coating materials and encapsulation techniques used to protect anthocyanin in butterfly pea flowers, as well as to evaluate their effects on the final product's stability, characteristics, and physicochemical properties. Literature search were conducted through PubMed, ScienceDirect, Scopus, and SpringerLink using structured keywords, following the inclusion criteria based on the Population, Concept, Context (PCC) framework and the PRISMA-ScR protocol. A total 7 published articles met the inclusion criteria. The results show that combination gelatin with coating materials such as pectin or maltodextrin was effective and commonly used. The use combination of gelatin+pectin or gelatin+maltodextrin with freeze drying is capable of forming a strong film, binding anthocyanin, stabilising colour, and proceting anthocyanin from degradation due to its low-temperature process, resulting in high encapsulation efficiency, high retention, and good morphology and particele size. In conclusion, no ideal coating material and encapsulation techniques. Further in vivo bioavailability studies are warranted to evaluate the most promising combinations, gelatin + pectin or gelatin + maltodextrin with freeze drying.